Quantification of CYP3A and Drug Transporters Activity in Healthy Young, Healthy Elderly and Chronic Kidney Disease Elderly Patients by a Microdose Cocktail Approach - Rattanacheeworn, Punyabhorn; Kerr, Stephen J; Kittanamongkolchai, Wonngarm; Townamchai, Natavudh; Udomkarnjananun, Suwasin; Praditpornsilpa, Kearkiat; Thanusuwannasak, Thanundorn; Udomnilobol, Udomsak; Jianmongkol, Suree; Ongpipattanakul, Boonsri; Prueksaritanont, Thomayant; Avihingsanon, Yingyos; et al. (Frontiers in Pharmacology, 2021)
Background: Ageing and chronic kidney disease (CKD) affect pharmacokinetic (PK) parameters. Since mechanisms are related and remain unclear, cytochrome P450 (CYP) 3A and drug transporter activities were investigated in the elderly with or without CKD and compared to healthy adults using a microdose cocktail. Methods: Healthy young participants (n = 20), healthy elderly participants (n = 16) and elderly patients with CKD (n = 17) received, in study period 1, a single dose of microdose cocktail probe containing 30 µg midazolam, 750 µg dabigatran etexilate, 100 µg atorvastatin, 10 µg pitavastatin, and 50 µg rosuvastatin. After a 14-day wash-out period, healthy young participants continued to study period 2 with the microdose cocktail plus rifampicin. PK parameters including area under the plasma concentration-time curve (AUC), maximum plasma drug concentration (Cmax), and half-life were estimated before making pairwise comparisons of geometric mean ratios (GMR) between groups. Results: AUC and Cmax GMR (95% confidence interval; CI) of midazolam, a CYP3A probe substrate, were increased 2.30 (1.70-3.09) and 2.90 (2.16-3.88) fold in healthy elderly and elderly patients with CKD, respectively, together with a prolonged half-life. AUC and Cmax GMR (95%CI) of atorvastatin, another CYP3A substrate, was increased 2.14 (1.52-3.02) fold in healthy elderly and 4.15 (2.98-5.79) fold in elderly patients with CKD, indicating decreased CYP3A activity related to ageing. Associated AUC changes in the probe drug whose activity could be modified by intestinal P-glycoprotein (P-gp) activity, dabigatran etexilate, were observed in patients with CKD. However, whether the activity of pitavastatin and rosuvastatin is modified by organic anion transporting polypeptide 1B (OATP1B) and of breast cancer resistance protein (BCRP), respectively, in elderly participants with or without CKD was inconclusive. Conclusions: CYP3A activity is reduced in ageing. Intestinal P-gp function might be affected by CKD, but further confirmation appears warranted Clinical Trial Registration: http://www.thaiclinicaltrials.org/ (TCTR 20180312002 registered on March 07, 2018)